Epistaxis: diagnóstico y alternativas terapéuticas actuales - Naser G., Alfredo; Aedo B., Cristián (Revista Hospital Clínico Universidad de Chile, 2007)
The epistaxis is one of the most common emergencies. While most of these bleeding can be resolved successfully by emergency medical, epistaxis some are complex and may require intervention by specialists with intensive management and hospitalization. There are multiple risk factors to produce an epistaxis, and this can affect any age group. The epistaxis is not alien morbidity able to get to the death if not resolved quickly hemorrhagic shock. The treatment strategies have generally been similar for decades. But with the advent of surgical nasal endoscopy and evolving methods of angiography and selective embolization, have allowed new options for handling fast and highly effective. In this review we reviewed and discussed the various alternatives for managing the epistaxis starting with those easy resolutions to those intractable. It discusses the pros and cons of the new techniques.